2005
DOI: 10.1227/01.neu.0000153925.96889.8a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prior Statin Use on Functional Outcome and Delayed Vasospasm after Acute Aneurysmal Subarachnoid Hemorrhage: A Matched Controlled Cohort Study

Abstract: SAH statin users demonstrated significant improvement in 14-day functional outcome, a significantly lower incidence of DCI and cerebral infarctions of any type, as well as prevention of TCD highest mean velocity elevation. However, we did not find a significant statin impact on mortality or global outcome (Modified Rankin Scale) in this small sample. This study provides clinical evidence for the potential therapeutic benefit of statins after acute SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 59 publications
(58 reference statements)
3
62
1
4
Order By: Relevance
“…This concept is supported by the study conducted by Lynch et al 7 The results reported by Ogilvy et al 17 do not support this finding; however, once again, their results did show a trend toward decreased mortality in patients who received statin therapy. This finding does contradict the results of a retrospective cohort study conducted by Parra and colleagues, 18 who found no significant difference in mortality at 14 days between patients who received statins and those who did not. The NNT calculated from our study for this outcome is 6.7, which is very low and strongly supportive of statin use after aneurysmal SAH.…”
Section: Sillberg Et Al Do Statins Improve Outcome After Aneurysmal Sah?contrasting
confidence: 81%
See 2 more Smart Citations
“…This concept is supported by the study conducted by Lynch et al 7 The results reported by Ogilvy et al 17 do not support this finding; however, once again, their results did show a trend toward decreased mortality in patients who received statin therapy. This finding does contradict the results of a retrospective cohort study conducted by Parra and colleagues, 18 who found no significant difference in mortality at 14 days between patients who received statins and those who did not. The NNT calculated from our study for this outcome is 6.7, which is very low and strongly supportive of statin use after aneurysmal SAH.…”
Section: Sillberg Et Al Do Statins Improve Outcome After Aneurysmal Sah?contrasting
confidence: 81%
“…One study by McGirt et al 16 (Nϭ115 patients) reported an 11-fold decrease in the incidence of vasospasm among patients who had received statin therapy for at least 1 month before SAH and who continued to receive statin therapy throughout their hospital stay. A second study by Parra et al 18 (Nϭ60 patients) Figure. Forest plot for studies reporting (a) the overall incidence of vasospasm, (b) the incidence of vasospasm-related delayed ischemic deficits, and (c) overall mortality.…”
Section: Sillberg Et Al Do Statins Improve Outcome After Aneurysmal Sah?mentioning
confidence: 91%
See 1 more Smart Citation
“…Perhaps its fibrinolytic 201 or anti-platelet 202 properties account for its success. Statins protect against DID 203,204 and have also been found to reduce microclot formation after brain injury 205,206 .…”
Section: Proximately 30% Of Patients Develop Signs Of Cerebral Ischemiamentioning
confidence: 99%
“…Statins have pleiotropic effects targeting many processes in the pathogenesis of vasospasm and reduce post-SAH vasospasm in animal models 1 and pilot human studies. [2][3][4] We conducted a prospective, randomized, double-blind study of the safety and feasibility of simvastatin treatment after SAH.…”
mentioning
confidence: 99%